2019
DOI: 10.1186/s40663-019-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

A fine-scale assessment of the ecosystem service-disservice dichotomy in the context of urban ecosystems affected by alien plant invasions

Abstract: Background: Natural resources within and around urban landscapes are under increasing pressure from ongoing urbanisation, and management efforts aimed at ensuring the sustainable provision of ecosystem services (ES) are an important response. Given the limited resources available for assessing urban ES in many cities, practical approaches for integrating ES in decision-making process are needed. Methods: We apply remote sensing techniques (integrating LiDAR data with high-resolution multispectral imagery) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Guerin et al (2018), for example, suggested that meta-analyses quantifying the impact of alien species might not be fully objective, as these studies are often characterised by selection bias toward highly deleterious taxa (but see also Kuebbing and Nuñez 2018, who argued that potential publication biases do not necessarily invalidate findings). Another potential consequence is the risk of implementing controversial management policies: management decisions based only on deleterious impacts ignore the fact that there might be conflicts of interest among stakeholders (Zengeya et al 2017;Potgieter et al 2019a;Kumschick et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Guerin et al (2018), for example, suggested that meta-analyses quantifying the impact of alien species might not be fully objective, as these studies are often characterised by selection bias toward highly deleterious taxa (but see also Kuebbing and Nuñez 2018, who argued that potential publication biases do not necessarily invalidate findings). Another potential consequence is the risk of implementing controversial management policies: management decisions based only on deleterious impacts ignore the fact that there might be conflicts of interest among stakeholders (Zengeya et al 2017;Potgieter et al 2019a;Kumschick et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological impacts consist of all UED that cause negative feelings or emotions, such as discomfort, anxiety or fear due to, for example, animal excrement or plant litter causing disgust (Lyytimäki et al 2008;Agbenyega et al 2009;Limburg et al 2010) or feelings of insecurity and fear of bodily harm when in urban green spaces (Tzoulas et al 2007;Hofmann et al 2012;Delshammar et al 2015;Shackleton et al 2015). For many urban residents, areas with uncontrolled or overgrown vegetation instil feelings of anxiety and fear, since these spaces can provide cover for dangerous or unattractive wildlife, such as snakes, spiders and insects, and facilitate crime or criminal activity by providing cover for criminals (Lyytimäki 2014;Shackleton et al 2015;Lyytimäki 2017;Escobedo et al 2018;Potgieter et al 2019a). The expansion of urban areas into natural ones and the promotion of recreational outdoor activities can create an overlap of habitats which has led to increased human-wildlife conflicts (Bombieri et al 2019).…”
Section: Psychological Impactsmentioning
confidence: 99%
“…In both Global North and South countries, studies have found that people experienced a fear of crime or being victims of crime in urban green spaces (Jansson et al 2013;Sreetheran and Van Den Bosch 2014;Shackleton et al 2015;Sreetheran and Van Den Bosch 2015;Lyytimäki 2017;Mouratidis 2019) and often these negative emotions lead to residents limiting their use of such spaces. Potgieter et al (2019a) found that criminal activity was unevenly distributed across the urban landscape of Cape Town and was either facilitated or limited by topographical features, such as hills, dunes or waterbodies, and physical features of the landscape, such as vegetation structure or type. Fear of crime is more prevalent among woman than men (Sreetheran and Van Den Bosch 2014).…”
Section: Psychological Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important role of tall alien trees as the invasive species that exert the most negative impacts in urban contexts has been repeatedly highlighted (McLean et al 2017;Potgieter et al 2019a). Indeed large size, and specifically plant height, is one of the major predictors of the capacity of non-native plants to spread and become invasive (Pyšek et al 2012) as well as one of the main reasons for why non-native trees are among the most widespread and harmful invasive species worldwide (Bucharova and van Kleunen 2009;Richardson and Rejmánek 2011;Pyšek et al 2014;Rejmánek 2014).…”
Section: Patterns Of Species Richnessmentioning
confidence: 99%